The Adoption of Lean Principles to Reduce Resistance to Change in Transforming a Shipyard (Journal of Business Management and Accounting, 2016)
A Shipyard is trying to change, but facing employee Resistance to Change (RTC). Resistance is attributed to the dysfunctional organisational context in the form of technical and political/structural issues giving rise to non-conformance behaviour. An action research was conducted with the author as a participant researcher to understand and identify the underlying behaviour of the employees. Lean production was used as an intervention to re-couple tasks to behavioural elements. Resistance is due to incoherency of a person’s belief in established standards, giving rise to cognitive dissonance. Lean principles reduces dissonance, creating psychological flow in the workforce and the momentum for change. As a result, the shipyard managed to recovered the delay of a ship and delivered it on-time, with cost avoidance of RM63 million in liquidated damage. The Shipyard also managed to reduce the average delay for ships undergoing repair to 6 months, compared to previous average delay of 17 months. This research was a collaboration between the employees and the researcher to identify the source of RTC. The outcome is both, insightful in creating change and contribution to knowledge. The significance of this study is the realisation of how individuals and groups’ past behaviour can subconsciously challenge the existence of the organisation and better methods. The study provides an exploratory model on the workings of human behavioural elements in Lean production. The knowledge of how the researcher gained utility from resistance and mediate through the application of these techniques would be of considerable benefit to leaders of change management.